2006
DOI: 10.1002/ejlt.200501217
|View full text |Cite
|
Sign up to set email alerts
|

Convenient preparation of picolinyl derivatives from fatty acid esters

Abstract: It is essential to have simple rapid methods for the determination of fatty acid structures. Traditionally, fatty acids are analysed by gas chromatography using their methyl ester derivatives (FAME). However, their corresponding mass spectra exhibit molecular ions but are usually devoid of ions indicative of structural features and, notably, the position of double bounds on the aliphatic chains [1]. In the most useful approach to structure determination, the carboxyl group is derivatised with a reagent contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…Selected samples were analyzed with a Restek FAMEWAX column (Crossbond ® polyethylene glycol stationary phase, 30 m length, 0.25 mm internal diameter, 0.25 µm film thickness), with an oven program of 6°C min −1 from 100 to 230°C, followed by a 10 min hold, to confirm structural assignment because coelutions of polyunsaturated fatty acids were minimal with the FAMEWAX column. Following quantification of the FAMEs, double bond positions in predominant unsaturated fatty acids were further confirmed through analysis of picolinyl esters following the method of Dubois et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…Selected samples were analyzed with a Restek FAMEWAX column (Crossbond ® polyethylene glycol stationary phase, 30 m length, 0.25 mm internal diameter, 0.25 µm film thickness), with an oven program of 6°C min −1 from 100 to 230°C, followed by a 10 min hold, to confirm structural assignment because coelutions of polyunsaturated fatty acids were minimal with the FAMEWAX column. Following quantification of the FAMEs, double bond positions in predominant unsaturated fatty acids were further confirmed through analysis of picolinyl esters following the method of Dubois et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…The present method is based on the methodology developed for rapid preparation of fatty acid picolinyl esters [9,11], C 2 -C 4 n-alkyl esters and 2-methoxyethyl esters [10]. However, some improvements were also required.…”
Section: Advantages Of the Present One-step Methodsmentioning
confidence: 99%
“…Mild reaction conditions allowed complete derivatization, i.e., picolinyl ester from TAG and phospholipids, 2 min at room temperature [9]; and 2-methoxyethyl and n-alkyl esters from TAG, 15 min at 40°C [10]. Dubois et al [11] reported complete derivatization of methyl esters to picolinyl esters in 45 min at 45°C. Because 9-anthrylmethyl esters are also esters of a primary alcohol, this methodology is applicable to their synthesis.…”
Section: Introductionmentioning
confidence: 98%
“…An alternative strategy for enhanced sensitivity is to improve the ionization effi ciency of FAs via specifi c derivatization with reagents that introduce either readily chargeable or fi xed charge groups such as tertiary or quaternary amines, respectively. Many derivatives of this nature have been reported including: pyrolidides (19)(20)(21), picolinyl esters ( 22,23 ), dimethyloxazolines (24)(25)(26)(27)(28), benzofurazans ( 29 ), pyridiniums ( 30 ), and cholines ( 31 ). The advantages of these derivatives include improved MS sensitivity and reproducible chromatography profi les.…”
Section: Preparation Of Fa Stock Solutionsmentioning
confidence: 99%